Antarctic Climate Research Data, Part 6 : Aerological Sounding Data at Asuka Station, Antarctica from January 1989 to October 1991 - KANETO, Susumu; AZUMA, Nobuhiko; MESHIDA, Shigemi; IWASAKI, Akira; SUKEGAWA, Yoshitaka; YAMANOUCHI, Takashi (National Institute of Polar Research, 1997)
P(論文) departmental bulletin paper